Nuclear Politics : Energy and the State in the United States, Sweden, and France. - Jasper, James M. (Princeton legacy library., 2014)
Why did nuclear energy policies in France, Sweden, and the United States, very similar at the time of the oil crisis of 1973 and 1974, diverge so greatly in the following years? In answering this question, James Jasper challenges one of the most popular trends in political analysis: explanations relying exclusively on political and economic structures to account for public policies. Jasper proposes a new cultural and state-centered approach--one heeding not only structural factors but cultural meanings, individual biographies, and elite discretion. Surveying the period from the successful c.